Flare gas reduction through electricity production. Issue 21 (1st November 2016) - Iora, P.; Bombarda, P.; Gómez Aláez, S. L.; Invernizzi, C.; Rajabloo, T.; Silva, P.
ABSTRACT: This article analyzed the potential energy recovery from rather small quantities of associated gas (<2000 m 3 /h), where the on-site electricity generation within the oil extraction field may represent a cost-effective solution as an alternative to flare combustion. Various power plant technologies were considered and compared from both the economic and avoided CO2 emissions points of view. It turned out that adopting a scheme with non-derated internal-combustion engines (ICE) fed by treated gas, and partial gas flaring, the most cost-effective result was obtained, showing a payback time of about 5 years and an internal rate of return (IRR) of 42.2%.